2003
DOI: 10.1590/s1516-44462003000600008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da estratégia de simulação mental sobre o controle postural

Abstract: A construção e manipulação espacial de imagens corporais têm origem basicamente visual e somato-motora. No entanto, a contribuição relativa de cada modalidade sensorial nos processos de simulação mental pode variar. Sirigu e Duhamel (2001) propuseram que a estratégia utilizada durante a simulação mental de movimentos produziria a ativação de circuitos neurais distintos. Neste estudo, investigamos o efeito da estratégia adotada na simulação mental de uma tarefa motora que envolve ajustes posturais utilizando as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
2
8
0
8
Order By: Relevance
“…Fear has shown influence on the ability to perform gait MI [41]. Studies have shown that kinesthetic MI presents a modulation effect on orthostatic postural control [7][8][9], depending on the vividness of the imagined movement [10], corroborating our results, since the participants also presented high levels of vividness (KVIQ). The present study also showed that the FoF during the tasks of kinesthetic MI (cervical flexion and inclination) is able to modulate the CoP variables, increasing their oscillation, which indicates greater postural imbalance (Figure 2A,B).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Fear has shown influence on the ability to perform gait MI [41]. Studies have shown that kinesthetic MI presents a modulation effect on orthostatic postural control [7][8][9], depending on the vividness of the imagined movement [10], corroborating our results, since the participants also presented high levels of vividness (KVIQ). The present study also showed that the FoF during the tasks of kinesthetic MI (cervical flexion and inclination) is able to modulate the CoP variables, increasing their oscillation, which indicates greater postural imbalance (Figure 2A,B).…”
Section: Discussionsupporting
confidence: 89%
“…For example, when an individual performs and imagines walking at a fixed distance, the time spent is similar, with no statistical difference [40]. Similarly, the number of repetitions of the same executed and imagined task in a "fixed time window" also presents no statistical difference [7,9,10]. Although the sample (n = 20) also has shown similarity between the execution and imagination of the tasks (cervical flexion and inclination) when comparing the number of repetitions (principle of isochronia), this same similarity was not observed when comparing the sensation of FoF between execution and imagination, indicating that the MI induces a greater modulation in the sensation of FoF in relation to the execution of the same tasks (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postural control relies on the integration of multiple sensory systems and on the active generation of muscle force along the body axis (Horak and Nashner, 1986; Peterka, 2002). Recent investigations have revealed that postural control is also influenced by high-level cognitive processes such as the mental simulation of a movement or motor imagery (Rodrigues et al, 2003, 2010; Grangeon et al, 2011). Motor imagery can be defined as a particular mental state in which dynamic, time-evolving images of actions are generated without a corresponding overt execution (Jeannerod, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Em sessões de treinamento mental, a IM tem sido apontada como responsável pelo aumento de habilidades motoras em atividades esportivas como o voleibol 3 e críquete 4 , embora a prática real demonstre melhores resultados do que o treinamento mental 5 . A IM tem origem basicamente visual e cinesté-sica 6 , sendo a modalidade visual correspondente à simulação mental de uma determinada tarefa motora como se estivesse observando um "vídeo mental", enquanto que, na IM cinestésica, o sujeito deve "sentir" como se o seu corpo estivesse em movimento, procurando obter sensações relacionadas às contrações musculares e da posição dos diversos segmentos corporais no espaço. Dentre os protocolos utilizados no estudo da IM, destacam-se os questioná-rios, na maioria das vezes relacionados ao grau de nitidez ou percepção da IM.…”
unclassified